2017
DOI: 10.7554/elife.25062
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity training enhances executive function in children in a randomized, placebo-controlled trial

Abstract: Background: Exercise-induced cognitive improvements have traditionally been observed following aerobic exercise interventions; that is, sustained sessions of moderate intensity. Here, we tested the effect of a 6 week high-intensity training (HIT) regimen on measures of cognitive control and working memory in a multicenter, randomized (1:1 allocation), placebo-controlled trial. Methods: 318 children aged 7-13 years were randomly assigned to a HIT or an active control group matched for enjoyment and motivation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 112 publications
2
78
2
1
Order By: Relevance
“…In addition, we found that the bleep test (the most intense activity) was, in general, no different from the control activity of taking a break outside the classroom but was not as beneficial as the SPA. High Intensity Training (HIT) is known to be beneficial for cognitive function in children, although the impact differs between individuals [35]. Recent evidence in adults shows that preference for higher intensity activity is predictive of affective response [36]-i.e.…”
Section: Relation To Previous Literaturementioning
confidence: 99%
“…In addition, we found that the bleep test (the most intense activity) was, in general, no different from the control activity of taking a break outside the classroom but was not as beneficial as the SPA. High Intensity Training (HIT) is known to be beneficial for cognitive function in children, although the impact differs between individuals [35]. Recent evidence in adults shows that preference for higher intensity activity is predictive of affective response [36]-i.e.…”
Section: Relation To Previous Literaturementioning
confidence: 99%
“…A sub-set of pupils from a sub-set of schools will also take part in a brain imaging sub-study which is embedded in the trial. Data for the brain imaging sub-study are collected at baseline (end of Year 7, pupils aged 11-12), after 12 months (end of Year 8, pupils aged 12-13) and at 24 months (end of Year 9, pupils aged [13][14].…”
Section: Designmentioning
confidence: 99%
“…Meanwhile, intervention studies in schools have found some evidence that programmes of aerobic exercise can lead to improved cognitive performance, particularly in the domains of attention and executive functions (working memory, cognitive flexibility, and inhibitory control) [11][12][13][14][15][16][17]. Separately, there are associations between objectively measured PA and academic attainment among adolescents [18] and indications that school-based exercise interventions can improve educational outcomes in this age group [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim and colleagues (2018) showed that a single bout of exercise session can enhances BDNF levels and improves memory performance in middle-aged women [13]. Similarly, it was also reported that chronic exercise interventions-induced BDNF increase and memory improvement in elderly [16].…”
Section: Introductionmentioning
confidence: 98%